Patterns of women's leadership in early Christianity - Taylor, Joan E. 1958- (Oxford University Press, 2021)
This authoritative collection brings together the latest thinking on women's leadership in early Christianity. Featuring contributors from key thinkers in the fields of Christian history, it considers the evidence for ways in which women exercised leadership in churches from the 1st to the 9th centuries CE.
Keywords: Women in Christianity-Middle Ages; Christian leadership; Frühchristentum; Kirchliches Amt; Frau; Electronic books; Aufsatzsammlung